The influence of size on winery performance: Evidence from Italy - Ricardo Sellers Rubio; Veronica Alampi Sottini (Wine Economics and Policy, 2016)
The aim of this paper is to analyse the influence of firm size on the economic performance of wineries. To achieve this, the paper employs both different traditional profitability and productivity measures and a non-parametric technique to estimate efficiency as indicators of performance. Further, several parametric and non-parametric tests are used to analyse the influence of firm size on these performance indicators. Overall, the results obtained with a sample of 723 Italian wineries (limited companies and cooperatives) in 2013 show that size has a positive influence on the economic performance of wineries. Managers should be aware of the importance of monitoring their own performance in order to guarantee the competitiveness of their wineries.
Keywords: 330; Efficiency; Italy; Performance; Productivity; Profitability; Winery